Effect of transformational leadership and organizational culture on employee performance mediated by job motivation - Putra, G. Ngurah Suteja; Dewi, I Gusti Ayu Manuati (International research journal of management, IT and social sciences, 2019)
This study aims to analyze the effect of transformational leadership and organizational culture on employee performance mediated by job motivation. The population in this study included 134 Civil Servants in the Secretariat of the Bali District/City Election Commission with a total sample of 100 people using the proportional random sampling method. Data analysis techniques were performed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. Job motivation is able to mediate the relationship between transformational leadership and organizational culture on employee performance partially. The Head of the Secretariat of the KPU of Regency/City in Bali needs to develop a transformational leadership style by providing motivation that inspires subordinates to work better when job motivation increases will be directly proportional to an increase in employee performance. In addition, a strong organizational culture such as information disclosure and participation of all members of the organization in achieving organizational goals can be developed continuously. When job motivation increases, it will encourage employees to improve the quality and timeliness of employees in completing work.